Dental bleaching and composite resin restaurations – case report - Lamas- Lara, César (2016)
The dental bleaching is a procedure that provides good clinical results, but sometimes there is a need to combine the bleaching with other procedures in order to optimize the results such as the use of composite restorations. The present case report describes the application of the dental bleaching procedures by carbamide peroxide 16 % and direct restorations with composite resin in the resolution of a clinical case. The aim was to describe correctly the bleaching technique using trays combined with the application of composite resins in a clear and simple way. The result was satisfactory for the patient since it was possible to bleach the teeth and improve their shape, returning to a color more suitable for the patient´s age. It is possible to conclude that the proper managing of the dental bleach combined with the direct restorations of composite resin offering a safe and effective alternative. KIRU. 2016 jul-dic; 13(2): 173-177.